STK11/LKB1 Modulation of the Immune Response in Lung Cancer: From Biology to Therapeutic Impact - Elvire Pons-Tostivint; Alexandre Lugat; Jean-François Fontenau; Marc Guillaume Denis; Jaafar Bennouna (Cells, 2021)
The STK11/LKB1 gene codes for liver kinase B1 (STK11/LKB1), a highly conserved serine/threonine kinase involved in many energy-related cellular processes. The canonical tumor-suppressive role for STK11/LKB1 involves the activation of AMPK-related kinases, a master regulator of cell survival during stress conditions. In pre-clinical models, inactivation of STK11/LKB1 leads to the progression of lung cancer with the acquisition of metastatic properties. Moreover, preclinical and clinical data have shown that inactivation of STK11/LKB1 is associated with an inert tumor immune microenvironment, with a reduced density of infiltrating cytotoxic CD8+ T lymphocytes, a lower expression of PD-(L)1, and a neutrophil-enriched tumor microenvironment. In this review, we first describe the biological function of STK11/LKB1 and the role of its inactivation in cancer cells. We report descriptive epidemiology, co-occurring genomic alterations, and prognostic impact for lung cancer patients. Finally, we discuss recent data based on pre-clinical models and lung cancer cohorts analyzing the results of STK11/LKB1 alterations on the immune system and response or resistance to immune checkpoint inhibitors.